The Initial Dioxigenase Gene Squences Analysis of Marine Bacteria Strain M128 - Muhamad Sahlan; Hanif Yuliani; Heri Hermansyah; Anondho Wijanarko (Department of Chemical Engineering, Universitas Gadjah Mada, 2013)
Biodegradation of polyaromatic hydrocarbons (PAHs) are catalyzed by multicomponent enzymes from microbe. The initial dioxygenase was used as a key enzyme for attacking the aromatic ring structure of PAHs, furthermore its initial dioxygenase gene was used to select PAHs degrading bacteria. Marine bacteria M128 strain could grow on medium contained PAHs. Detection of its cellular initial deoxygenase gene was done by nahAc gene amplification. The nahAc gene commonly used as biomarkers of PAH degradation, and as a result, nahAc gene sequence analysis of marine bacteria M128 strain was similar to naphthalene dioxygenase of Pseudomonas genera with 99% homology.